2015
DOI: 10.1002/jso.24028
|View full text |Cite
|
Sign up to set email alerts
|

Breast reconstruction and adjuvant therapy: A systematic review of surgical outcomes

Abstract: PMRT was associated with an increased incidence of adverse events when compared to chemotherapy. There was little evidence to suggest that adverse events following breast reconstruction were related to adjuvant chemotherapy. Manipulating the method and timing of reconstruction may mitigate some of the undesirable outcomes associated with PMRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 84 publications
3
77
1
6
Order By: Relevance
“…However, the group with the irradiated permanent implants had significantly increased grade IV capsular contracture rates (6.3% vs. 1.2%; P < 0.01). These results, are consistent with a recent systematic review and pooled analysis that demonstrated that PMRT to permanent implants reduces the rate of reconstructive failure (18.8% vs. 14.7%; P < 0.01) [39]. Despite this, irradiating the tissue expander remains common as many patients that receive neoadjuvant chemotherapy are not candidates for delaying PMRT until after the exchange procedure.…”
Section: Surgical Outcomessupporting
confidence: 90%
“…However, the group with the irradiated permanent implants had significantly increased grade IV capsular contracture rates (6.3% vs. 1.2%; P < 0.01). These results, are consistent with a recent systematic review and pooled analysis that demonstrated that PMRT to permanent implants reduces the rate of reconstructive failure (18.8% vs. 14.7%; P < 0.01) [39]. Despite this, irradiating the tissue expander remains common as many patients that receive neoadjuvant chemotherapy are not candidates for delaying PMRT until after the exchange procedure.…”
Section: Surgical Outcomessupporting
confidence: 90%
“…Multiple studies have reported on the increased morbidity associated with all forms of immediate breast reconstruction in the setting of PMRT 57 . Early studies on flap exposure to radiation found significant rates of flap fibrosis, fat necrosis, and shrinkage which in severe cases could necessitate flap replacement 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is multifactorial but likely related to its technical feasibility, lack of donor site morbidity, and changes in mastectomy patterns, such as increased bilateral mastectomies. Despite these advantages, risk of potential complications and unsatisfactory long term aesthetic outcomes are significantly increased as compared to autologous reconstruction [13,30] . In this review, capsular contracture, poor cosmesis, persistent pain, and infection were the most commonly cited reasons for patients choosing to undergo tertiary reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic reconstruction is the most common method of breast reconstruction and has increased at a rate of 5% a year [12] . Despite its increasing popularity, complications leading to poor aesthetics, persistent pain, and implant loss are not uncommon, particularly in the setting of adjuvant radiotherapy [13,14] . In addition to alleviating implant-related complications, autologous conversion may provide a more natural appearance and improve longevity of the reconstructed breast.…”
Section: Introductionmentioning
confidence: 99%